Idiopathic toe walking: what should a general paediatrician know about it?. (29th September 2015) - Mittal, R
Abstract : Background: Idiopathic toe walking (ITW) is defined as a condition in which children walk with a tip-toe gait pattern after the age of 2 years without evidence of neurologic, orthopaedic or psychiatric disease. Untreated, persistent toe-walking may place children at increased risk for falling or developing limitations in ankle mobility and structural abnormalities. However, there is little published literature on the natural history of this condition. Aims: To raise awareness about the natural history of ITW and the treatment options among paediatricians. Methods: It is a retrospective study. Patients were identified from physiotherapy department database. Results: There were 40 patients (M:F 2.3:1). 63% were referred directly to physiotherapists, 27% to paediatricians and rest 10% to orthopaedicians. Age of referral varied from 13 months to 9 years (mean=4.2 years). No foot or toe abnormalities were identified on routine first day neonatal examination. Expressive speech was delayed in nine patients (22.5%).Family history was positive in 25% cases. All patients were advised dorsiflexion exercises and stretches to tendoachillis and hamstrings. 29 patients (72%) were given Pedro boots, 19 were given foot insoles (47%). One patient was given AFO splint. 18 children (45%) were given serial castings. Five patients did not need any orthotic help. All children were followed up by physiotherapists. Mean duration of follow up was 2.5 years (range 6 months to 6.5 years). No child has required surgical correction so far. Five cases were discharged from follow up. Residual toe-walking is still present in 35 children. Conclusions: ITW is a well defined clinical entity with strong family history. Speech delay is an important association with ITW. A significant proportion requires physiotherapy input for long time with nearly half needing serial casting. Further follow up would help define natural history and outcome of these patients.